Expression of tissue transglutaminase in Balb-C 3T3 fibroblasts: effects on cellular morphology and adhesion (The Rockefeller University Press, 1992)
Tissue transglutaminase is a cytosolic enzyme whose primary function is to catalyze the covalent cross-linking of proteins. To investigate the functions of this enzyme in physiological systems, we have established lines of Balb-C 3T3 fibroblasts stably transfected with a constitutive tissue transglutaminase expression plasmid. Several cell lines expressing high levels of catalytically active tissue transglutaminase have been isolated and characterized. Transglutaminase-transfected cells showed morphologic features quite distinct from their nontransfected counterparts. Many of the cells showed an extended and very flattened morphology that reflected increased adhesion of the cells to the substratum. Other cells, particularly those showing the highest levels of intracellular transglutaminase expression, showed extensive membrane blebbing and cellular fragmentation. The results of these experiments suggest that the induction and activation of tissue transglutaminase may contribute both to changes in cellular morphology and adhesiveness.